Language immersion programme: an analysis of Indonesian students’ reflections on learning experiences at a Malaysian International University - Abdul Rahim, Nor Elena; Md. Zamin, Ainul Azmin; Baharudin, Muhammad Danial (Malaysian English Language Teaching Association (MELTA), 2025)
English Immersive Programmes offer learners an authentic exposure to the target language. Malaysia offers a culturally familiar ESL environment for learners of English from non-native neighbouring countries. The study examines the reflections of a group of high school students from Sumatra who participated in a two-week language immersion programme at an international university in Malaysia. The language programme was designed to integrate both indoor and outdoor activities into the learning process. A total of twelve journals were collected and analysed using Braun and Clark’s (2006) thematic analysis. Learning, Emotional Journey, and Cultural Encounters were identified as the main themes, with Language as a sub-theme of Learning. The findings affirm the role of immersion on all four language skills and suggests that reflective journaling can foster learners’ development in language learning. To assist students in future programmes, a comprehensive needs analysis prior to implementation is essential, allowing suitable courses and activities to be designed and offered.